PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PASIEN RAWAT INAP DI RUMAH SAKIT DR. H. IBNU SUTOWO BATURAJA - DAHLIA DAHLIA (Jurnal Manajemen Bisnis Unbara, 2020)
The aim of this research is to analize the influence of service quality and price to inpatient’s satisfaction. The research was conducted by distributing questionnaires to 166 responden taken by using purposive sampling technic. This research analyzed by using multiple linear regresion analysis method. The result of this research indicates that service quality and price have positive and significant influence to satisfaction with price as the dominant variable.